Pengaruh pelatihan kader yandu lansia dalam menciptakan desa ramah dan sehat bagi lansia di Desa Purwobinangun, Sleman - Sumarni Sumarni; Adi Heru Sutomo; Cempaka Tursina; Purwanta Purwanta; Ade Indah Wahdini; Nanda Kusumaningrum (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Merapi eruption can cause a psychological traumatic for elderly such as depression, increasedisability, and decrease quality of life. We need to train the cadres to make an elderly care village. The aim of this study is to know the influence of cadre training in knowledge and skill for elderly healthiness. This study uses secondary data from community research on May until September 2018 in Desa Purwobinangun, Sleman. The target is cadres and 80 elderlies in Desa Purwobinangun, Sleman. The instruments in this study such as Module Ramah dan Sehat Lansia, Geriatric Depression Scale (GDS), Mini Mental State Examination(MMSE), questionnaire about knowledge and skills of a traditional games, and questionnaire about early detection and treatment in old age health. The data will be shown in quantitative data. After trained, the average value of the knowledge of coping with local cultural wisdom games, social and religious support, brain gymnastics, and friendly elderly increased by 30 points, 50 points, 40 points, and 50 points respectively.Changes in the average value of the skills of elderly yandu cadres in tackling local cultural wisdom games, social and religious support, brain gymnastics, and friendly elderly have increased by 17.12 points, 19.18 points, 28.68 points, and 27.58 points. For changes in the trend of health problems, the elderly who are not hypertensive increased by 7 people, for the elderly who have diabetes mellitus there was no change in the number before and after training, while the elderly who experienced depression fell by 18 people. For the elderly who experience cognitive impairment decreased by 18 people and elderly who have high quality of life increased by 22 elderly. Yandu training for the elderly can improve the knowledge and skills of the elderly yandu cadre in the management of health problems in the elderly. Cadres empowerment can increase knowledge and skill of cadre to treat health problem in elderly